The Effect of Audit Quality on Stock Crash Risk in Tehran Stock Exchange - Khajavi, Shokrollah; Zare, Akbar (International Journal of Economics and Financial Issues, 2016)
This paper aims to examine the impact of audit quality on stock crash risk in Tehran Stock Exchange. Down-to-up volatility (DUVOL) and whether or not experience crash month (CRASH) have been used as two criteria to measure stock crash risk. In addition, auditor industry specialization has been considered as an indicator of audit quality. The hypotheses are tested by using data from 74 firms listed in the Tehran Stock Exchange from the year 2003 to 2013, multivariate linear regression, and logistic regression method. The results indicate that there is a negative and significant relationship between audit quality and down-to-up volatility. On the other hand, there is an insignificant negative relationship between audit quality and crash. Recent scandals in Iran show that the audit quality level in Iran is very low. On the other side, the Stock Exchange does not have a long history and stock market is not efficient either. As such, the stock crash risk is significant for current and potential investors. However, stock crash risk has not been examined in Iran as it should be. So this article tries to cover this phenomenon. Keywords: Audit quality; Stock crash risk; Down-to-up volatility (DUVOL); whether or not experience crash month (CRASH); Auditor expertise. JEL Classifications: M41; M42